REDUCING MENSTRUAL PAIN IN ADOLESCENTS: THE EFFECT OF DARK CHOCOLATE CONSUMPTION - Nuraeni, Rina; Marmi, Marmi; Ayu, Windri Dewi; Heni, Heni; Wasiyat, Sri (Journal of Maternity Care and Reproductive Health, 2026)
Primary dysmenorrhea is a common problem among adolescent girls and may negatively affect daily activities, emotional well-being, and academic performance. Various non-pharmacological approaches have been explored to manage menstrual pain with minimal side effects, including the consumption of dark chocolate, which contains magnesium and bioactive compounds associated with pain modulation and neuromuscular relaxation. However, evidence regarding structured dark chocolate consumption in early adolescent populations, particularly within school-based settings in semi-urban areas of Indonesia, remains limited, and optimal dosing schedules and implementation under nursing supervision have not been sufficiently explored. This study aimed to examine the effect of dark chocolate consumption on the reduction of primary dysmenorrhea pain intensity among adolescent girls. Methods: A pre-experimental study with a one-group pretest–posttest design was conducted among 30 seventh-grade female students who experienced primary dysmenorrhea. Participants consumed dark chocolate consumption with ≥70% cocoa content at a total dose of 30 grams per day, divided into three intakes per day, for two consecutive days during the first and second days of menstruation. Pain intensity was measured using a numerical rating scale before the first consumption (pretest) and after completion of the intervention (posttest). Data were analyzed using univariate analysis and the Wilcoxon signed-rank test to assess changes in pain intensity following the intervention. The findings demonstrated a statistically and clinically significant reduction in dysmenorrhea pain intensity within the study sample. The mean pain score decreased markedly from 6.13 prior to the intervention to 3.70 after dark chocolate consumption, reflecting a transition from moderate to mild pain levels among most participants. Wilcoxon signed-rank analysis confirmed that this reduction was significant (p < 0.05), indicating that the observed improvement represented a consistent and meaningful change across the sample rather than random variation. Dark chocolate consumption was associated with a significant reduction in primary dysmenorrhea pain among adolescent girls. These findings support the use of dark chocolate as a simple, acceptable, and low-risk non-pharmacological intervention.